Pengaruh Media 3D Folding Paper Crafts Terhadap Hasil Belajar IPAS Siswa Kelas V Gugus VIII Kota Bengkulu - Kurniasari, Herlin; Dalifa; Susanti, Atika (JURIDIKDAS, 2024)
This study aims to determine the influence of 3D folding paper crafts media on the learning outcomes of the water cycle learning topic for fifth-grade students in Cluster VIII, Bengkulu City. This research is a quantitative study using a quasi-experimental research method and The Matching Only Pretest-Posttest Control Group Design. The population in this study is fifth-grade students in Cluster VIII, Bengkulu City. The sample consists of students from Class V at SDN 34 Bengkulu City as the experimental class and students from Class VB at SDN 36 Bengkulu City as the control class, obtained through cluster random sampling. The technique used in this study is a pre-test and post-test designed in the form of 10 multiple-choice questions. The results of the hypothesis test in the experimental class show that the t-value using Equal Variances Assumed= 2.799, and the Sig. (2-tailed) value is 0.008, with a ttabel distribution value of 2.069. Thus, thitung> ttabel (2.799 > 2.069) and Sig.(2-tailed) 0.008< 0.05. This data indicates that there is a difference in learning outcomes between the experimental class and the control class due to the different treatments applied to both classes.Based on this, it can be concluded that there is an influence of 3D folding paper crafts media on the knowledge aspect of learning outcomes in the water cycle topic for fifth-grade students in Cluster VIII, Bengkulu City.